2016
DOI: 10.1007/jhep01(2016)147
|View full text |Cite
|
Sign up to set email alerts
|

Holographic competition of phases and superconductivity

Abstract: We use a holographic theory to model and study the competition of four phases: an antiferromagnetic phase, a superconducting phase, a metallic phase and a striped phase, using as control parameters temperature and a doping-like parameter. We analyse the various instabilities and determine the possible phases. One class of phase diagrams, that we analyse in detail, is similar to that of high-temperature superconductors as well as other strange metal materials.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 107 publications
4
80
0
1
Order By: Relevance
“…Study along the similar line has been reported very recently in Ref. [19], where a different system with an extra Uð1Þ gauge field on the gravity background is introduced to represent a chemical potential, as an external tuning parameter for the phase transition in high temperature superconductors. This is an example of modeling the phase transitions in reality due to varying a tunable doping parameter.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Study along the similar line has been reported very recently in Ref. [19], where a different system with an extra Uð1Þ gauge field on the gravity background is introduced to represent a chemical potential, as an external tuning parameter for the phase transition in high temperature superconductors. This is an example of modeling the phase transitions in reality due to varying a tunable doping parameter.…”
Section: Introductionmentioning
confidence: 56%
“…Finally, we would like to emphasize the difference between our minimal model and the model in Ref. [19]. Instead of using the specific holographic models of superconductor and anti ferro-magnetism as in Ref.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is completely plausible to generalize the construction in our current simple model to more complicated cases, for instance, taking the interactions between two gauge fields into account, or including a charged scalar field [34] to study the cuprate phase diagram [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The results, on the contrary, indicate that there is little universality, as by varying the contents of the bulk theory one can dramatically alter the IR behaviour -e. g. reproducing on demand the entire phase diagram of the cuprates with all the four main phases as well as the domains of their coexistence in the extended EM model with the additional vector and scalar fields which represent the competing orders [79,80].…”
Section: D+z-θmentioning
confidence: 99%